Non-invasive Bioluminescence Monitoring of Hepatocellular Carcinoma Therapy in an HCR Mouse Model - Zhao, Zhu; Dai, Juji; Yu, Yan; Zhang, Qian; Liu, Sai; Huang, Guanmeng; Zhang, Zheng; Chen, Tianke; Pan, Rulu; Lu, Liting; Zhang, Wenyi; Liao, Wanqin; et al. (Frontiers in Oncology, 2019)
Animal models play crucial roles in the development of anticancer therapeutics. The ability to quickly assess the localized primary hepatocellular carcinoma (HCC) status in a noninvasive manner would significantly improve the effectiveness of anti-HCC therapeutic studies. However, to date, animal models with this advantage are extremely scarce. In this study, we developed a novel animal model for the fast assessment of drug efficacy against primary HCC in vivo. HCC was induced in immunocompetent hepatocarcinogenesis reporter (HCR) mice by diethylnitrosamine (DEN) injection and confirmed by histopathological staining. Using the bioluminescence imaging (BLI) technique, HCC progression was longitudinally visualized and monitored in a noninvasive way. Tests of two clinical drugs showed that both sorafenib and oxaliplatin significantly inhibited the BLI signal in mouse liver in a dose-dependent manner. The in vivo intensity of BLI signals was highly consistent with the final tumour burden status in mouse liver after drug treatment. The inhibitory effect of anti-HCC drugs was accurately evaluated through in vivo BLI intensity detection. Our study successfully established a bioluminescence mouse model for noninvasive real-time monitoring of HCC therapy, and this HCR mouse model would be a useful tool for potential anti-HCC drug screening and new therapeutic strategy development.